Surgery on Call - Edited by Lefor, Alan T. and Gomella, Leonard G. (Sedney McGraw-Hill, 2003)
This quick reference presents the necessary core information for hands-on management and diagnosis for non-specialists. A logically organised quick-access reference to the management of 77 most common surgical on-call problems, with cross-section of relevant specialist care, distilling the relevant practical information.
Include Index
Keywords: Surgery -- Diagnosis, Surgical -- Emergency medicine--Diagnosis -- Medical emergencies -- Diagnosis